A Method of Integrated Energy Metering Simulation Data Generation Algorithm Based on Variational Autoencoder WGAN. Issue 1 (1st February 2022) - Zhang, Penghe; Xue, Yang; Song, Runan; Yang, Yining; Wang, Cong; Yang, Liu
Abstract: With the development of integrated energy systems, the penetration rate of all types of distributed power sources continues to increase. In a grid oriented to integrated energy metering, the metering business of different energy sources needs to fully consider the dynamic characteristics of different user loads. This paper aims at the generation of large-scale integrated energy metering data in large-scale integrated energy digital simulation technology, starting from supporting the construction of an integrated energy metering simulation system, combining various business applications and artificial intelligence technology under the background of the energy Internet. For the requirements of energy metering simulation, a method of integrated energy metering simulation data generation based on variational autoencoder WGAN is proposed, and the effect of the method proposed in this paper is verified through actual metering scene data.